Paradigma Kualitatif sebagai Landasan Berpikir Pendidikan Kewarganegaraan - Pratama, Febri Fajar; Mutia, Dhian (Department of Pancasila and Civic Education, Universitas Negeri Medan, 2020)
This article is a study that discusses and examines the concept of qualitative research paradigms in the realm of Citizenship Education science which has been dominated by the tradition of positivistic. The conception of truth which is the subject of a paradigm is reviewed through the perspective of the philosophy of science, from the ontological, epistemological and axiological point of view using the method of literature review. Citizenship Education as a scientific discipline that studies humans as material for study today is still much influenced by positivistic traditions that are identical with numbers and statistics. Citizenship Education experiences an epistemological crisis in terms of theory, but in essence, Citizenship Education aims to create good citizens, so that the need for theory as a result of the tradition of paradigmatic thinking which emphasize qualitative approach is very crucial.———————- Artikel ini merupakan studi untuk memahami dan mengkaji konsep paradigma penelitian kualitatif dalam ranah keilmuan Pendidikan Kewarganegaraan yang selama ini didominasi oleh tradisi positivistik. Konsepsi mengenai kebenaran yang menjadi bahasan paradigma ditinjau melalui sudut pandang filosofis ilmu pengetahuan, yakni dari segi ontologis, epistimologis dan aksiologis dengan menggunakan metode studi literatur. Pendidikan Kewarganegaraan sebagai disiplin ilmu yang mempelajari manusia sebagai bahan kajiannya saat ini masih banyak dipengaruhi tradisi positivistik yang identik dengan angka dan statistika. Pendidikan Kewarganegaraan mengalami krisis epistimologis dalam segi teori, padahal hakikatnya, Pendidikan Kewarganegaraan bertujuan untuk terwujudnya warga negara yang baik, sehingga kebutuhan teori sebagai hasil dari tradisi berpikir paradigmatik yang menekankan pendekatan kualitatif sangat krusial.